A fixed-point type result for some non-differentiable Fredholm integral equations - Hernández-Verón, Miguel A.; Singh, Sukhjit; Martínez, Eulalia; Yadav, Nisha (Mathematical Modelling and Analysis, 2024)
In this paper, we present a new fixed-point result to draw conclusions about the existence and uniqueness of the solution for a nonlinear Fredholm integral equation of the second kind with non-differentiable Nemytskii operator. To do this, we will transform the problem of locating a fixed point for an integral operator into the problem of locating a solution of an integral equation. Thus, assuming conditions on the Nemytskii operator, we will obtain a global convergence domain for the solution of the considered integral equation, taking for this a uniparametric family of derivativefree iterative processes with quadratic convergence. This result provides us a new fixed-point result for the integral operator considered.